Factibilidad para la implementación de una empresa productora y distribuidora de papas precocidas a la francesa en la Ciudad de Loja - Chamba Cueva, Jonathan Jorge (2016)
This research was carried out with the purpose of determining the "FEASIBILITY FOR THE IMPLEMENTATION OF A PRODUCTION AND DISTRIBUIDORA COMPANY OF PREOCOCATE POPES TO FRENCH IN THE CITY OF SHOP". Taking into consideration the present theme, the objective was to carry out a feasibility study, with the purpose of determining the feasibility when deciding the implementation of the same in the city of Loja. For the study of the present project different materials, methods and research techniques were used, which were used to analyze all the information collected and then to carry out a concrete study of the whole project, the survey technique was taken into account Which was applied to the various food establishments to date in the city of Loja, the same made up of Restaurants, Burguérs and Cafes giving a total of 1006 establishments, with a sample of 247 surveys to the applicants and 28 surveys to the bidders Of the product precooked potatoes. The market study analyzed the demand and the offer to determine the reception of the product called potatoes precooked to the French "DON CHIKI" in the local market. Resulting in an effective demand of 469,851 kilos of potatoes precooked to the French and an unsatisfied demand of 464,079 kilos of precooked potatoes, once this was determined, a technician was carried out where the installed capacity of the project was determined Which will be 1'051,200 kilograms of precooked French potatoes and a capacity of 6 250,560 kilograms of precooked French potatoes equivalent to 23,83% of the total installed capacity for the first year and a capacity 33.83%, equivalent to 355,621 kilograms of precooked potatoes that will be produced from the second year to the fifth, the size and location, the project engineering, the plant layout, the organizational structure and the respective function manuals were determined. Which would help to implement a good administrative organization. In the financial study it was determined that the project will have an investment of $ 51,266.38 dollars and will be financed with a contribution of partners that will be 60.99% of the total investment, this percentage equivalent $ 31,266.38 and a loan That BAN ECUADOR was requested of 20,000.00 equivalent to 39.01% of the total amount of the investment, five years, with an interest rate of 15%. In the financial evaluation study, the financial indicators presented positive results to ensure a profitability of the project where it was calculated in VAN (Net Present Value) that is of 84,688.27 dollars, the IRR (Internal Rate of Return) of 66.81% , The RBC (Cost Benefit Ratio) of 1.29 which means that for every dollar invested the company will have a profit of 0.29 cents, PRC (Capital Recovery Period) that will be 1 year, 6 months, and 10 Days, and in the sensitivity analysis with a 16.20% increase in costs and a sensitivity analysis with a decrease in income of 12.47% giving in these percentages the two analyzes a 0.99 which means that in At this point the company will not suffer changes or alterations. 7 Finally, we proceeded with the conclusions where it was determined to have reached the objectives and feasibility when deciding to implement a company producing and distributing potatoes precooked to the French in the city of Loja. We proceeded with the recommendations that emphasize the implementation of the project, the bibliography that was used to carry out the research work and the corresponding annexes that are a component to attest to the completion of the project.